Legal implications for the regulation of ownership, storage and control of narcotics in Indonesia - Hatarto Pakpahan; I Nyoman Nurjaya; Setiawan Nurdayasakti; Nurini Aprilianda (International Review of Social Sciences Research)
The purpose of this study is to examine the effects of the Narcotics Law Articles 111, 112, 117, and 122 on the use of drugs for recreational purposes, with focus on individuals who possess, store, and regulate narcotics. This study used a normative legal research strategy, which involves analysing legal texts, regulations, and court decisions. We collected and analysed data from statutory laws, legal commentaries, and case studies to assess the practical application of these provisions. The findings suggest that despite their noble intentions, these articles often lead to severe punishments for individual users without distinguishing them from large-scale traffickers. Drawing from the experiences of nations like the Netherlands and Portugal, this research proposes legislative reforms to create more equitable and efficient drug control policies in Indonesia, emphasising rehabilitation over punishment.